HABITAT OPTIMALIZATION OF CAPTIVE DEER PT. PUSRI PALEMBANG - Rahmania, Nadya; Yustian, Indra; Setiawan, Arum (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2017)
Deer is one of the species that going through a reduction of population because its being used as the target of illegal hunting. To prevent the reduction in population, the efforts to save them with conservation method both in-situ or ex-situ has been done. Captive deer in PT. Pusri Palembang is the only captive deer which located in urban areas of Palembang and carrying out an ex-situ conservation effort. This research aimed to analyze the habitat condition such as daily feed, water needed, and shelter, to know about the level of palatability and also to analyze the habitat condition as a basic of captive deer management towards an optimalization. The research has been done in January 2015. The interview method, literature study and field observation are used to get the data about population and habitat condition in captive deer PT. Pusri Palembang. It can be concluded that the habitat condition in the captive deer PT. Pusri Palembang still quite good, and 1,5 hectare areas still be able to maintain the total of 44 deers (22 sambar deers and 22 chital deers) in 2015.Key words: sambar deer, chital deer, captivity, ex-situ conservation, PT Pusri Palembang.Â